(3eaGJjM GdLfGf heUGHjM GdLfGfs - (3GdHQShj GdMfaj, jYbhH Hf Ydj, J (B931 (3g` s ((3bdGhR Hf eMeO Hf UGQh eMeOs)
(3ChdgG (B:s
(3MeOG def ef Ydi YHGOg fYeI GdESdGe hHYO ajbhd jYbhH Hf SjO Ydj hCf ef Hjf GdcJH TQYI GdESdGe aLGA HMeO Gddg TQMG Ydi GdTCf Ldj GdYQaGf hSejJg HeaGJjM GdLfGf heUGHjM GdLfGfs
(3BNQgG (B:s
(3eMGVQGJ ddTjN GdEeGe CHj GdbGSe GdMSjf Hf GdeaVd GdTgjQ HQGZH GdCUagGfj aj TQM TGajI ddehdi GdaGVd GdeYQha HLGQHQOjs
(3Hg WjGQGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 8 / 201s
(3eYLe GdeDdajf(B: 4 / 130s
(3cTa GdXfhf(B: 2 / 1044s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs